Guinea-Bissau : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2005)
This 2004 Article IV Consultation highlights that Guinea-Bissau's economic performance has weakened substantially in recent years. Real GDP declined by 7 percent in 2002 and was flat in 2003. Structural reforms stalled after the war; the private sector remained incapacitated because of the destruction of equipment and infrastructure caused by the conflict, and the loss of stocks owing to confiscating and looting. In 2003, the external current account deficit, excluding official transfers, halved relative to the previous year, to 6.7 percent of GDP, reflecting higher cashew nut exports and stagnating imports.